Exposure to endosulfan increases endothelial permeability by transcellular and paracellular pathways in relation to cardiovascular diseases. (April 2017) - Xu, Dan; Liu, Tong; Lin, Limei; Li, Shuai; Hang, Xiaoming; Sun, Yeqing
Abstract: Exposure to environmental pollutants results in out-of-balance of vascular homeostasis. Endothelial dysfunction leads to a disruption of the endothelial permeability characteristics, associated with cardiovascular diseases. We previously reported that endosulfan could cause endothelial dysfunction, but the role of endosulfan in permeability of endothelial cells has been unexplored. To elucidate molecular mechanism of endosulfan-induced changes in endothelial permeability, human umbilical vein endothelial cells (HUVECs) were exposed to endosulfan, followed by endothelial permeability analysis. The results showed that permeability of HUVECs was enhanced at 48 h after exposure to endosulfan in a dose-dependent manner. Immunofluorescence analysis demonstrated the disruptions of actin cytoskeleton and focal adhesion in endosulfan-exposed cells. Endosulfan activated MMP3/LAMC1/FAK signaling pathway, and downregulated ROCK and PXN in transcellular pathway. Endosulfan affected adherens junctions via E-cadherin and β-catenin, and impaired gap junctions through downregulation of Cx43 in paracellular pathway. We predicted four closely related human cardiovascular diseases in Nextbio, including shock, coronary arteriosclerosis, disorder of cardiac function and hypertensive disorder in relation to endosulfan exposure. Some genes such as ROCK2 and PXN were predicted to be key genes in these diseases. These findings suggest that endosulfan increased endothelial permeability by paracellular and transcellular pathways, implicating the potential correlation between endosulfan and cardiovascular diseases. Graphical abstract: Highlights: Endosulfan enhances endothelial permeability in HUVECs. Endosulfan disrupts actin cytoskeleton and focal adhesion. Endosulfan affects adherens junctions and impaired gap junctions. Cardiovascular diseases are predicted to correlate with endosulfan exposure.